Investigation of gene–environment interactions between vitamin D and colorectal cancer susceptibility genetic variants in large bowel epithelium. (25th February 2016) - Vaughan-Shaw, Peter G; Grimes, Graeme; Ochocka, Anna-Maria; Dunbar, Karen; Timofeeva, Maria; Din, Fahrat V N; Farrington, Susan M; Dunlop, Malcolm G
Abstract: Background: Observational data implicate vitamin D deficiency in the aetiology of colorectal cancer, yet causality is not established. In-house epidemiological data suggest that the colorectal cancer susceptibility locus rs9929218 might interact with vitamin D concentration to impact risk. This single nucleotide polymorphism is also intronic within CDH1, a tumour suppressor gene. This study aimed to determine whether vitamin D impacts on expression of CDH1 and interacts with common genetic variance linked to colorectal cancer susceptibility. Methods: Ten cell lines were treated with calcitriol (50 nM) for 16 h and induction of CDH1 assessed with real-time PCR. Colorectal epithelial organoids (three mouse, three human) were cultured and the effect of calcitriol (0·5–100 nM, 16–24 h) investigated. Samples from normal colorectal mucosa were taken from 110 study participants, and the association between vitamin D concentration and rs9929218 genotype with gene expression assessed (HT12 microarray). A subgroup underwent vitamin D supplementation (3200 IU orally) and repeat sampling at 6 and 12 weeks. Findings: Calcitriol treatment increased CDH1 expression in five cell lines (1·3–2·8-fold, p<0·05). Basal CDH1 expression was associated with the rs9929218 genotype (GG 3·96 units [SD 3·41], AA 1·02 [1·24]; p=0·03), but induction of CDH1 with calcitriol was not. Colorectal organoids were cultured for up to 6 weeks. Calcitriol increased CDH1 expression in human (1·9-fold [SD 0·28], p=0·02) but not murine organoids. Strong correlation between VDR and CDH1 expression ( r =0·74 p<1 × 10 −5 ) was seen in human colorectal mucosa with a weaker correlation between vitamin D concentration and VDR expression ( r =0·22, p=0·009). GG genotype was associated with increased CDH1 (p=0·046) and VDR expression (p=0·015). Vitamin D supplements increased vitamin D concentration (2·2-fold [SD 1·1], p=0·006) and VDR expression (1·06 [0·09], p=0·02) but not CDH1 expression. Interpretation: Our findings suggest that CDH1 expression in colorectal cancer cell lines is associated with rs9929218 genotype and is induced by calcitriol treatment, and that organoids offer potential as a biological model of normal colorectal mucosa. The correlation between CDH1 and VDR in normal human colorectal mucosa and the association with genotype further supports an interaction between vitamin D status, genotype at the rs9929218 locus, and CDH1 expression. The supplementation study is continuing and aims to demonstrate and further define this interaction. Funding: Medical Research Council, Royal College of Surgeons of England, Tenovus, Melville Trust for Care and Cure of Cancer, Mason Medical Research Trust.